2018
DOI: 10.1142/s0217979218300098
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heating rate, impurity concentration of Cu, atomic number, temperatures, time annealing temperature on the structure, crystallization temperature and crystallization process of Ni1−xCux bulk;x= 0.1, 0.3, 0.5, 0.7

Abstract: This paper studies the effects of heating rate 4 × 10[Formula: see text] K/s, 4 × 10[Formula: see text] K/s, 4 × 10[Formula: see text] K/s; impurity concentration of Cu on Ni[Formula: see text]Cu[Formula: see text] bulk with x = 0.1, x = 0.3, x = 0.5, x = 0.7; atom number (N), N = 4000 atoms, 5324 atoms, 6912 atoms, 8788 atoms at temperatures (T), T = 300 K; N = 6912 atoms at T = 300 K, 400 K, 500 K, 600 K, 700 K, 800 K; N = 6912 atoms at T = 600 K after time annealing temperature (t), t = 500 ps on the struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 65 publications
4
11
0
Order By: Relevance
“…Berendsen et al [65] have identified the transition temperature (T m ) of NiAu ranges from T m = 1100 K to T m = 1300 K with Au impurity concentration of 58% [66]. Combined with our recent results as Al [67], FeNi [68], AlNi [69], Ni 1−x Fe x [70], Ni 1−x Cu x [71], Ni [72,73], these results show that the transition temperature (T m ) of Ni material; T m is always proportional with atom number (N), N −1/3 [74,75], and the electronic structure of AuCu [76] and AgAu [77]. The phase transition of Ni material can be determined by stress or temperature [78][79][80][81], and the bonding length of Ni-Ni determined by the experimental method is r = 2.43 Å [82], while the simulation method of Dung, N.T is r = 2.45 Å [73], and P.H.…”
Section: Introductionsupporting
confidence: 78%
“…Berendsen et al [65] have identified the transition temperature (T m ) of NiAu ranges from T m = 1100 K to T m = 1300 K with Au impurity concentration of 58% [66]. Combined with our recent results as Al [67], FeNi [68], AlNi [69], Ni 1−x Fe x [70], Ni 1−x Cu x [71], Ni [72,73], these results show that the transition temperature (T m ) of Ni material; T m is always proportional with atom number (N), N −1/3 [74,75], and the electronic structure of AuCu [76] and AgAu [77]. The phase transition of Ni material can be determined by stress or temperature [78][79][80][81], and the bonding length of Ni-Ni determined by the experimental method is r = 2.43 Å [82], while the simulation method of Dung, N.T is r = 2.45 Å [73], and P.H.…”
Section: Introductionsupporting
confidence: 78%
“…e limit of elastic deformation σ e � E ABC ε e of alloy ABC is determined by [9] σ e � E ABC ε e � σ 0ABC ε α e 1 + ε e . (19) Here E ABC is Young's modulus of alloy ABC and has the form [5,6]…”
Section: Model and Theoretical Calculationsmentioning
confidence: 99%
“…Deformation mechanisms in the mechanical response of nanoporous gold are investigated by molecular dynamics simulations [16]. In addition, in recent years, some researchers have considered factors affecting the structure, the phase transformation, and the crystallization process of alloys AuCu [17], NiCu [18,19], and AgCu [20].…”
Section: Introductionmentioning
confidence: 99%
“…have successfully investigated the effect of Au dopant concentration on the optical properties of AgAu alloy. 18 Besides, in recent years, we have also studied the effects of heating rate, doping concentration, atom number, temperature of the structure, electronic structure, phase transition, and crystallization of alloys AuCu, 2 2 AlNi, 19 NiCu, 20 , 21 and FeNi. 22 23 The results obtained show that when the heating rate increases, the alloy changes from liquid state to amorphous state and vice versa, and that when the atom number increases, size increases and the energy of the system decreases.…”
Section: Introductionmentioning
confidence: 99%